First Meeting in Asia of the Asia Pacific Research Integrity Network - Barr, D (Account Res, 2020)
In 2017, the University of Hong Kong and the University of California San Diego co-hosted the first Asian meeting of the recently formed Asia Pacific Research Integrity (APRI) network in Hong Kong. Aligned with planning meetings in 2015 and 2016 funded in part by the US Office of Research Integrity (ORI), the Hong Kong meeting was designed by a multi-national planning committee to address pressing challenges in research integrity: improving multi-national communication; exchanging information on managing misconduct investigations; and sharing best practices to promote research integrity. To create a sustainable, robust international partnership to promote research integrity in the region, the purpose of this 2017 meeting was to foster multi-national awareness, understanding, and opportunities for collaboration. The meeting was defined by four objectives that emerged from the previous meetings: (1) Articulate differences as well as areas of common ground; (2) Identify best or recommended practices; (3) Identify opportunities for research or collaboration; and (4) Set an APRI network agenda for coming years. The key anticipated outcome was to advance the conversation surrounding research integrity among academic institutions and regulators in Asian and Pacific Rim nations. This outcome was evidenced by meeting participation, participant satisfaction, and articulation of next steps for the APRI network.